Assessment of the Antibiotic Resistance Profile, Genetic Heterogeneity and Biofilm Production of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolated from The Italian Swine Production Chain - Pedro Rodríguez-López; Virginia Filipello; Pierluigi Aldo Di Ciccio; Alessandra Pitozzi; Sergio Ghidini; Federico Scali; Adriana Ianieri; Emanuela Zanardi; Marina Nadia Losio; Ancuta Cezara Simon; Giovanni Loris Alborali (Foods, 2020)
The main aim of the present study was to evaluate the level of antibiotic resistance, prevalence and virulence features of methicillin-resistant Staphylococcus aureus (MRSA) isolated from heavy swine at abattoir level and farming environments in Lombardy (Northern Italy). With this scope, 88 different heavy swine farms were surveyed, obtaining a total of n = 440 animal swabs and n = 150 environmental swabs. A total of n = 87 MRSA isolates were obtained, with an overall MRSA incidence of 17.50% (n = 77) among animal samples and a 6.67% (n = 10) among environmental. Molecular characterisation using multilocus sequence typing (MLST) plus spa-typing showed that sequence type ST398/t899 and ST398/t011 were the most commonly isolated genotypes, although other relevant sequence types such as ST1 or ST97 were also found. A lack of susceptibility to penicillins, tetracycline and ceftiofur was detected in >91.95, 85.05 and 48.28% of the isolates, respectively. Resistance to doxycycline (32.18%), enrofloxacin (27.59%) and gentamicin (25.29%) was also observed. Additionally, a remarkable level of antibiotic multiresistance (AMR) was observed representing a 77.01% (n = 67) of the obtained isolates. Genetic analysis revealed that 97.70% and 77.01% of the isolates harboured at least one antibiotic resistance or enterotoxin gene, respectively, pointing out a high isolate virulence potential. Lastly, 55.17% (n = 48) were able to produce measurable amounts of biofilm after 24 h. In spite of the current programmes for antibiotic reduction in intensively farming, a still on-going high level of AMR and virulence potential in MRSA was demonstrated, making this pathogen a serious risk in swine production chain, highlighting once more the need to develop efficient, pathogen-specific control strategies.